Design and rationale for a speech and language treatment plan for children and adolescents diagnosed with or suspected of being abused, and their families - Pava-Ripoll, Nora Aneth; Useche Varela, Daisy Lisbeth; Ascuntar Piscal, Dayana Marcela; Forero Galvis, Michell Dayhana (Revista de Investigación en Logopedia, 2026)
Child abuse (CA) is a global public health problem with serious consequences for the communicative and neuropsychological development of children and adolescents (BA). Despite evidence of its impact, speech-language pathology has had little participation in its approach, especially in Colombia. The objective of this study is to establish and design a speech-language path of action contextualized to the Colombian case for the care of children and adolescents diagnosed or suspected of CA and their families, based on a trauma-informed approach. Mixed study with a sequential explanatory design. Phases1) a systematic literature review (n=34 articles), 2) qualitative interviews with health professionals (n=12), and 3) a theoretical-methodological integration process for the design of the path. The results show that the categories emerging from the systematic review and interviews revealed key gaps in speech-language pathology practice and the need for a trauma-informed restorative approach. From an ecosystemic-relational approach and a critical-constructivist ontoepistemology, the intervention is conceived as a restorative, compassionate, and contextual process, centered on children and adolescents and their care environments. The theoretical discussions guided the structuring of the pathway into three stages: promotion and prevention, acute phase, and repair. The proposal positions speech therapy as a key element in CA contexts. The need for trauma-informed and rights-oriented professional training is highlighted.